OFFICIAL GUIDE TO THE NATIONAL AIR AND SPACE MUSEUM - National Air and Space Museum. (Washington, D.C. : Published for the National Air and Space Museum by the Smithsonian Institution Press, 1988)
Includes bibliographical and references